Fontes e doses de magnésio nas culturas da soja e do milho - Carneiro, Leandro de Mello e Silva (2019)
The correct handling of soil fertility is important to reach the productive potential of the culture, but must take into account soil attributes, such as the Ca:Mg ratio. The experiments were installed in the agricultural area, belonging to the Agroeldorado Agriculture and Livestock LTDA, in the municipality of Uberlândia - MG, for the 2017/2018 harvest, aiming to evaluate the influence of different sources of Mg and the relation between calcium and magnesium in the cultivation of soybean and maize. In the first experiment with soybean, the experimental design was a completely randomized block, in factorial 5x3, being five Ca:Mg ratios, 1:1, 2:1, 3:1, 4:1 and 5:1 and three magnesian sources, oxisulphate of Mg, oxide of Mg and sulphate of Mg. In the second experiment with maize, it was used a randomized block design in a factorial scheme 4x3, with four Ca:Mg ratios, 1:1, 2:1, 3:1 and 4:1, and three magnesian sources, oxisulphate of Mg, oxide of Mg and sulphate of Mg. In two experiments were evaluated the contents of nutrients Ca2+, Mg2+ and K+ in the soil, the Ca:Mg ratio, the percentage of Mg in CEC and the leaf contents of Mg and the SPAD index, the productivity and the mass of one thousand grains. The results were submitted to analysis of variance by the Tukey test at 0.05 significance level. For soybeans, the Ca:Mg ratio, 1:1, and the sources of oxide of Mg and oxisulphate of Mg increases the percentage of Mg in CEC, while the relations 4:1 and 5:1 and the sources oxide of Mg and oxisulphate of Mg, are the ones that least alter the Ca:Mg relationship in the original soil. For corn, the Ca:Mg ratios 1:1, 2:1 and 3:1, and the sources of oxide of Mg and oxisulphate of Mg increases the percentage of Mg in the CEC, while relations 3:1 and 4:1 and the sources oxide of Mg and oxisulphate of Mg, are the ones that least alter the Ca:Mg relationship in the original soil.